2019
DOI: 10.1098/rspb.2019.0091
|View full text |Cite
|
Sign up to set email alerts
|

Does exceptional preservation distort our view of disparity in the fossil record?

Abstract: How much of evolutionary history is lost because of the unevenness of the fossil record? Lagerstätten, sites which have historically yielded exceptionally preserved fossils, provide remarkable, yet distorting insights into past life. When examining macroevolutionary trends in the fossil record, they can generate an uneven sampling signal for taxonomic diversity; by comparison, their effect on morphological variety (disparity) is poorly understood. We show here that lagerstätten impact the disparity of ichthyos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
5
20
0
Order By: Relevance
“…In addition, a recent study of ichthyosaur morphological disparity showed that patterns are generally consistent even when taxa known only from exceptionally fossiliferous formations are removed (Flannery Sutherland et al . 2019). In our study, it is clear that generic diversity is not directly linked with ecological disparity (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent study of ichthyosaur morphological disparity showed that patterns are generally consistent even when taxa known only from exceptionally fossiliferous formations are removed (Flannery Sutherland et al . 2019). In our study, it is clear that generic diversity is not directly linked with ecological disparity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2018; Flannery Sutherland et al . 2019; Moon & Stubbs 2020), ecospace modelling has only been used in one study of ichthyosaurs (Dick & Maxwell 2015). The aim of this study is to produce the first, holistic, high resolution record of ecospace occupancy and ecological disparity of marine tetrapods throughout the Mesozoic.…”
mentioning
confidence: 99%
“…Large amounts of missing data, usually above 25%, considerably reduce the overall distance between taxa that can be captured on ordination spaces on both empirical and simulated data sets 47,59 . To reduce the negative impact of missing data, we removed all characters with more than 30% of missing data from the data set, which resulted in a total of 19% missing data on the final data set—safely below the threshold of 25% 47,59,60 . Additionally, inapplicable characters are a big conceptual problem to construct a morphospace.…”
Section: Methodsmentioning
confidence: 99%
“…Missing data in correspondence analyses are typically handled via column average substitution. However, this can result in “centroid slippage” (Flannery Sutherland et al 2019), in which incomplete taxa plot closer to the origin than they should. This can be especially problematic when more than one major clade is being analyzed, as in this study, as missing values are reconstructed using all groups, potentially overinflating morphological disparity and creating phylogenetically incongruous scenarios.…”
Section: Methodsmentioning
confidence: 99%